Immunohistochemical expression of melanocytic and myofibroblastic markers and their molecular correlation in atypical fibroxanthomas and pleomorphic dermal sarcomas. (27th September 2018) - Helbig, Doris; Mauch, Cornelia; Buettner, Reinhard; Quaas, Alexander
Abstract : Background: Atypical fibroxanthomas (AFXs) and pleomorphic dermal sarcomas (PDSs) are UV‐induced pleomorphic skin tumors with a non‐specific immunoprofile. For that reason, exclusion of other dedifferentiated tumor entities by immunohistochemistry is still mandatory to avoid misdiagnosis. Methods: We determined the expression frequency of several melanocytic and myofibroblastic markers investigating 50 AFXs and PDSs.. Next‐generation‐sequencing (NGS) was performed in microphthalmia‐associated transcription factor (MiTF)‐expressing cases. Results: We identified one MiTF‐expressing AFX and PDS, and two PDSs harboring single S100‐positive dendritic cells whereas Melan A, HMB45, and SOX10 were negative. Calponin was moderately expressed by tumor giant cells in one PDS whereas h‐caldesmon, desmin, and myogenin were not expressed in any of the AFXs or PDSs. The MiTF‐positive AFX presented CDKN2A, OXA1L, and PDGFRA mutations whereas the PDS harbored a typical TP53 mutation. Both patients have not shown any tumor progression over the last 16 and 30 months. Conclusion: Rarely, AFX and PDS express the melanocytic marker MiTF and/or the myofibroblastic marker calponin. In doubtful cases, using a panel of immunohistochemical markers helps to avoid misdiagnosis.